Generation of highly entangled photon pairs for continuous variable Bell inequality violation - Zhang, L; U'Ren, AB; Erdmann, R; O'Donnell, K; Silberhorn, C; Banaszek, K; Walmsley, I (2007)
We propose a novel experimental technique based on the process of parametric downconversion for the generation of photon pairs characterized by ultra-high dimensional spectral entanglement. It is shown that a superlattice of nonlinear and linear segments can be exploited to obtain states exhibiting a remarkably large entanglement, with a Schmidt number in the region of 107. We furthermore consider the application of such highly entangled photon pairs for the violation of a Bell inequality constructed from a measurement of the transverse wavevector Wigner function; such an approach eliminates the need for filtering the photon pairs and consequently eliminates an important potential loophole.